Identification of small molecule inhibitors of the STAT3 signaling pathway: Insights into their structural features and mode of action. Issue 22 (15th November 2015) - Kim, Kyeojin; Kim, Su-Jung; Han, Young Taek; Hong, Sung-Jun; An, Hongchan; Chang, Dong-Jo; Kim, Taewoo; Lim, Bumhee; Lee, Jeeyeon; Surh, Young-Joon; Suh, Young-Ger
Graphical abstract: Abstract: A series of novel STAT3 inhibitors consisting of Michael acceptor has been identified through assays of the focused in-house library. In addition, their mode of action and structural feature responsible for the STAT3 inhibition were investigated. In particular, analog6 revealed promising STAT3 inhibitory activity in HeLa cell lines. The analog also exhibited selective inhibition of STAT3 phosphorylation without affecting STAT1 phosphorylation and cytostatic effect in human breast epithelial cells (MCF10A- ras ), which supports cancer cell-specific inhibitory properties.